Analysis of TACI mutations in CVID & RESPI patients who have inherited HLA B*44 or HLA*B8 - Zhuang Yingxin; Waldrep Manda L; Schroeder Harry W (BMC, 2009)
Abstract Background Recent reports have suggested that Common Variable Immunodeficieny (CVID) can present as an autosomal dominant trait dependent on the inheritance of a set of uncommon mutations/alleles of TACI (transmembrane activator and calcium-modulator and cyclophilin ligand interactor) involving exons 3 or 4. Penetrance, however, appears to be incomplete. Among our clinic population, the greatest genetic linkage for CVID is to the major histocompatibility complex (MHC) on chromosome 6. The majority of our patients have inherited HLA *DQ2, *DR7, *DR3(17), *B8, and/or *B44. Of these, HLA*B44 was present in almost half of the patients and was thus the most common susceptibility allele. HLA *B44 was also found to be over-represented among patients who presented to our clinic with adult-onset recurrent sinopulmonary infections (RESPI) and normal serum immunoglobulin levels, a cohort that included first and second degree relatives of patients with CVID. One of the two original reports of the association between TACI and CVID also reported Human Leukocyte Antigen (HLA) haplotypes. Of 13 affected subjects, nine had inherited HLA *B8 and six had inherited HLA B44. This raised the possibility that TACI mutations might synergize with MHC class I alleles to enhance susceptibility to humoral immune deficiency. Methods We identified 63 CVID patients irrespective of HLA status and 13 RESPI patients who had inherited HLA*B44. To evaluate for mutations in the gene for TACI, we PCR amplified and sequenced TACI exons 3 and 4 from these patients. Results Of the 76 patients, eleven proved heterozygous for a previously reported, silent T->G polymorphism [rs35062843] at proline 97 in exon 3. However, none of the 13 RESPI patients and only one of the 63 CVID patients inherited a TACI allele previously associated with CVID. This patient was heterozygous for the TACI A181E allele (exon 4). She did not carry *DQ2, *DR7, *DR3(17), *B8, or *B44. Conclusion These findings suggest that TACI mutations are unlikely to play a critical role in creating susceptibility to CVID among patients with previously recognized MHC class I and class II susceptibility alleles. Supported by NIH/USIDNET N01-AI30070, NIH R21 AI079741 and NIH M01-RR00032